Influence of biomass burning on the levels of atmospheric polycyclic aromatic hydrocarbons and their nitro derivatives in Chiang Mai, Thailand - Thanyarat Chuesaard (2018)
Chiang Mai and several other provinces in northern Thailand have been annually facing air pollution problems during the dry season. Ten polycyclic aromatic hydrocarbons (PAHs); 19 nitropolycyclic aromatic hydrocarbons (NPAHs); and levoglucosan (LG), a marker for biomass burning, were quantified in total suspended particulates (TSP) collected in Chiang Mai during the dry, transition, and wet seasons in 2010. The concentrations of PAHs and NPAHs in the dry season were significantly higher than in the wet season. The [Benzo[a]pyrene (BaP)] - [benzo[ghi]perylene (BghiPe)] ratio, as an indicator of traffic, and the correlations of PAHs and NPAHs with LG showed that biomass burning significantly contributes to air pollution in the dry season. 9-Nitroanthracene (9-NA) was the most abundant NPAH which suggests that 9-NA is generated from biomass burning. We proposed the [9-NA] - [1-nitropyrene (1-NP)] ratio as a new indicator for assessing the contribution of biomass burning. Biomass burning was a major source of PAHs and NPAHs in the dry season, whereas vehicle exhaust was the main contribution in the wet season. The high carcinogenic risks in the dry season correlate with more harmful air conditions during this season. Thus, it is important to control biomass burning to reduce air-pollution-related health risks during the dry season in northern Thailand. © Taiwan Association for Aerosol Research.